(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
This research explored the concept of the Blue Economy and its potential for sustainable development of ocean resources. It examined four key ideas: the Ignatian principle of “Tantum Quantum” (proper use, not abuse), stakeholder analysis, multidisciplinary approaches, and multiple intelligences theory. The research argued for a shift from shareholder-focused to stakeholder-inclusive models in managing ocean resources. It emphasized the importance of considering all affected parties, including non-human stakeholders like marine life. The multidisciplinary nature of ocean studies was highlighted, calling for collaboration across fields such as marine biology, economics, and ethics. The theory of multiple intelligences was applied to value diverse forms of knowledge, including traditional maritime skills. Major challenges facing the Blue Economy were discussed, including overfishing, pollution, and lack of governance in international waters. Recommendations included supporting fisher cooperatives in developing countries, improving export facilities, increasing plastic recycling, promoting coastal tourism, and recognizing the value of workers in the maritime sector. The research advocated for a balanced approach that promotes economic development while ensuring the long-term sustainability and health of ocean ecosystems.